The Role of the Subdistrict Chief of Phithen in Solving Wastewater Problems in the Community. Phithen Subdistrict, Thung Yang Daeng District, Pattani Province. - ตาลี, นิโรเบีย; วาเงาะ, ณานิสรา; แวยูโซะ, นูรมี; ผูหาดา, ฮากีม (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to study the role of the Subdistrict Administrative Organization Chairman in addressing wastewater problems in the community of Phithen Subdistrict, Thung Yang Daeng District, Pattani Province. A qualitative research methodology was used, collecting data through in-depth interviews with 13 key informants: the Subdistrict Administrative Organization Chairman, community leaders, and residents affected by the wastewater problem. Data was analyzed using content analysis. The research findings indicate that the primary cause of wastewater problems in Phithen Subdistrict is the operation of a bean sprout cultivation factory, which has led to the degradation of public water sources and community wells. From 2023 to 2024, the Subdistrict Administrative Organization Chairman played a crucial role in resolving the issue through policy formulation and planning, coordination with relevant agencies, legal oversight, and promoting public participation. These efforts have significantly reduced the severity of the wastewater problem and improved the quality of life for residents in the area.